Praxelis Clematidea (Griseb.) R.M. King & H. Rob. (Asteraceae): A New Allien Invasive Angiosperm Record for Bangladesh (Bangladesh Journal of Plant Taxonomy, 2024)
Abstract not available.Bangladesh J. Plant Taxon. 31(1): 181-185, 2024 (June)